Graphic visualization in printed media: how does the use of technology influence journalism culture - Sjafiie, Sri Syamsiyah Lestari; Hastjarjo, Sri; Muktiyo, Widodo; Pawito, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Technological change has changed readers’ desire to get news information. Present generation readers prefer to read more efficient news. Visual communication through infographics accompanying a news story becomes an effort that printed media take to fulfill consumer need to understand the news content faster and easier. Competing with other media, newspapers definitely try to provide completeness of news content to readers. It is now prevalence for newspapers to use graphics to explain or visualize news story. Graphics visualization which could be sketch, maps, or chart will give added value to news story and could help readers to understand news content faster. Technology makes it possible. Different from old-fashioned newspapers, today's newspapers are more colorful. It affects journalists’ value and practices. When the habit to read news story is shifting to be more visual, is journalism culture shifting as well? Journalists are supposed to prepare detail materials to make graphics visualization more accurate by using technology. Will the trusted values and journalism practices also change along with the shift of news content that is more visual? How the use of technology influences journalism culture is the focus of this paper. This research explains how technology had changed part of journalism practices, especially in visualization graphics. The facts that in the past were illustrated through text narration and pictures, are now illustrated through infographics. Journalism culture has changed.